2011
DOI: 10.1007/s00455-011-9384-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Dysphagia in Inflammatory Muscle Diseases Resulting from Impaired Suprahyoid Musculature

Abstract: Dysphagia has previously been reported in the inflammatory myopathies (IMs): inclusion body myositis (IBM), dermatomyositis (DM), and polymyositis (PM). Patients report coughing, choking, and bolus sticking in the pharynx. Myotomy has been the treatment of choice, with variable success reported. We sought to determine underlying causes of dysphagia in IM patients using instrumental evaluation. Eighteen subjects participated in the study: four with DM, six with PM, and eight with IBM. They underwent simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 32 publications
3
41
0
1
Order By: Relevance
“…The mechanism of dysphagia of DM remains unclear. A recent study using VFSS and manometry indicated that dysphagia in inflammatory muscle diseases may be due to impaired muscle contraction and reduced hyolaryngeal excursion than the often held belief of failed upper esophageal sphincter relaxation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of dysphagia of DM remains unclear. A recent study using VFSS and manometry indicated that dysphagia in inflammatory muscle diseases may be due to impaired muscle contraction and reduced hyolaryngeal excursion than the often held belief of failed upper esophageal sphincter relaxation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cricopharyngeomyotomy is used when the underlying mechanisms of dysphagia is failed relaxation of the upper esophageal sphincter. This intervention may not be beneficial with normal relaxation and other mechanisms of dysphagia, i.e., delayed swallow initiation and decreased hyolaryngeal excursion ( 138 ). Other interventions include percutaneous endoscopic gastrostomy (PEG), pharyngoesophageal dilatation, and injection of botulinum toxin ( 139 141 ).…”
Section: Treatmentmentioning
confidence: 99%
“…However, scleroderma and DM-PM significantly surpass the other CTDs concerning this complication, due to the fact that both diseases are characterized by pathophysiologic mechanisms seriously predisposing to impaired function of swallowing and thus to overt acute aspiration or occult chronic microaspiration of oropharyngeal and/or gastropharyngeal contents [143,184]. In scleroderma, the gastrointestinal tract is the internal system most commonly involved.…”
Section: Acute Gastroesophageal Content Aspiration Pneumonitismentioning
confidence: 99%
“…Poor oral hygiene, tooth loss, decreased saliva production, and periodontal disease are also frequently encountered in scleroderma patients, further aggravating the risk of aspiration pneumonia [187]. In DM-PM, on the other hand, dysphagia seems to be mostly related to impaired muscle contraction, reduced hyoid-laryngeal excursion, and/or failed upper esophageal sphincter relaxation [19,143,188]. …”
Section: Acute Gastroesophageal Content Aspiration Pneumonitismentioning
confidence: 99%
See 1 more Smart Citation